(untitled) (Scientific journal of the Fergana State University, 2023)
This article is dedicated to the existence of graduonymy, which is considered as one of the modern linguistics’ new notions, in syntax. Moreover, graduonymic relations among syntactic units and phenomena, and their peculiarities are investigated; they are proved by some examples.